MENDIDIK ANAK DALAM PERSPEKTIF IBNU SINA: GAGASAN DAN PEMIKIRANNYA - Junaidi Arsyad (JURNAL RAUDHAH, 2019)
Discussing ideas and thoughts of Ibn Sina will be confronted with various fields of science that he developed. One of them is about children's education because he is also an education expert, besides being a doctor, scientist and philosopher. This study aims to examine the ideas and thoughts of Ibn Sina related to educating children. By using descriptive analytical methods, the way it works starts from gathering the required reading material, sorting and selecting relevant reading material, studying the reading material, then making the writing framework as desired in the method, Ibnu Sina's ideas and thoughts were discovered. about educating children. According to him, in the process of teaching and learning to children, educators should first start from learning the Qur'an. At the same time, children are also told to learn the spelling of letters, memorize verses and proverbs. After they are good at reading, memorizing the Qur'an and mastering Arabic lessons, they are directed to subjects that are in accordance with their talents so that the desired Islamic education goals are achieved.